2010
DOI: 10.2174/187153010791213047
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate and Metabolic Syndrome

Abstract: The fibric acid derivative, fenofibrate (FF) has been used in the US since 1998 to manage patients with dyslipidemia. Typical changes in serum lipids as a result of FF treatment include clinically important mean reductions of serum triglycerides (TG) by a mean change of −93.7 mg/dL (−39.3%), increases of high density lipoprotein cholesterol (HDLC) by +5.5 mg/dL (+12.4%), and reductions in low density lipoprotein cholesterol (LDLC) by −17.9 mg/dL (−12.3%). The greatest reductions in serum TG are usually observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 105 publications
3
19
0
Order By: Relevance
“…However, the success rate in the intensive medical therapy group did not differ significantly from that of conventional treatment group in the latter years of the follow-up period, and a Kaplan–Meier analysis did not show a significant difference in MetS risk between the treatment groups. Studies in both animals and humans have suggested that treatment with metformin, [28] captopril, [29,30] valsartan, [31,32] simvastatin, [33] or fenofibrate [34,35] alone reduced the development of MetS, which is largely consistent with our findings. Because MetS increases the risk of cardiovascular disease, [3638] it seems unlikely that improvements in MetS indicators contributed to a lower risk of subclinical atherosclerosis in the intensive medical therapy group, compared with that in the conventional treatment group.…”
Section: Discussionsupporting
confidence: 91%
“…However, the success rate in the intensive medical therapy group did not differ significantly from that of conventional treatment group in the latter years of the follow-up period, and a Kaplan–Meier analysis did not show a significant difference in MetS risk between the treatment groups. Studies in both animals and humans have suggested that treatment with metformin, [28] captopril, [29,30] valsartan, [31,32] simvastatin, [33] or fenofibrate [34,35] alone reduced the development of MetS, which is largely consistent with our findings. Because MetS increases the risk of cardiovascular disease, [3638] it seems unlikely that improvements in MetS indicators contributed to a lower risk of subclinical atherosclerosis in the intensive medical therapy group, compared with that in the conventional treatment group.…”
Section: Discussionsupporting
confidence: 91%
“…49-52 Clinical studies suggested that the therapeutic benefits of PPARγ ligands are mediated in part by the release of adiponectin. 53 Diabetic patients and patients with coronary heart disease have elevated levels of adiponectin after exposure to thiazolidinediones, which reduce cholesterol levels and improve hypertension control.…”
Section: The Role Of Ppars In Metabolic Syn-dromementioning
confidence: 99%
“…These two organisations including ADA advocated the use of fibrates to reduce TG and elevate HDL-C in patients with the MS or diabetes and suggested that fenofibrate combination with statin may be an effective and safer alternative than statin alone. In 2010, in a review, fenofibrate is of benefit in the treatment of dyslipidemia, especially among those with MS [12]. Another study, the same year, reported that both atorvastatin and fenofibrate exhibited multidirectional pleiotropic effects in subjects with MS [13].…”
Section: Discussionmentioning
confidence: 99%